THE INFLUENCE OF INTERNAL CONTROL SYSTEMS, IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS, AND HUMAN RESOURCE COMPETENCE ON FINANCIAL REPORT QUALITY - Kartika, Vio Nanda; Ningsih, Sri (JURNAL AKUNTANSI DAN AUDITING, 2024)
This research aims to empirically explore the interaction between internal control mechanisms, adherence to government accounting standards, and human resource proficiency in Jember Regency, focusing on their combined effects on the quality of government financial reports. The study collected data from individuals working in the financial or accounting departments of 24 SKPDs (Local Government Work Units) in Jember Regency. Through a comprehensive questionnaire-based approach, 100 respondents participated in the study. Data analysis employed multiple linear regression techniques. The results reveal that the Internal Control System did not significantly affect financial statement quality. However, the implementation of Government Accounting Standards and the competency of human resources had notable impacts on financial statement quality. These findings underscore the importance of full compliance with Government Accounting Standards and the presence of skilled human resources to enhance financial reporting quality in government organizations.